The Development of Technology in Supporting the Implementation of Forensic Accounting and Investigative Auditing in Fraud Detection (A Study of the United States, the United Kingdom, China, Indonesia, and Nigeria) - Devisa, Fitrah; Purwanto, Agus (Dinasti International Journal of Economics, Finance & Accounting, 2025)
In the current era of globalization and digitalization, maintaining financial integrity and preventing fraud has become increasingly challenging. Fraudulent activities are no longer confined to individual actors but have evolved into systematic and cross-border organizational networks. As a response, forensic accounting and investigative auditing have emerged as vital tools in the detection and prevention of fraud. With rapid technological advancements, traditional audit approaches are undergoing a significant transformation, incorporating innovations such as Artificial Intelligence (AI), Big Data Analytics, and Blockchain. This study aims to examine the development of technology in supporting the application of forensic accounting and investigative auditing for fraud detection and prevention in five countries: the United States, the United Kingdom, China, Indonesia, and Nigeria. A qualitative-descriptive literature study method was employed, analyzing 40 reputable international journal articles published between 2020 and 2025. The findings reveal that technologies like AI, Big Data, and Blockchain have significantly enhanced the effectiveness of fraud detection, particularly in developed countries. However, developing nations such as Indonesia and Nigeria face critical challenges, including limited infrastructure, regulatory gaps, and low technological literacy. The study concludes that the integration of technology-based forensic accounting and investigative auditing can strengthen financial oversight systems. This research contributes to the development of an adaptive anti-fraud technology framework tailored to each country's institutional context and represents the first cross-country study to integrate the Fraud Pentagon Theory with technological advancements in auditing on a global scale.